Neurodevelopmental outcomes of 3-year-old children exposed to maternal SARS-CoV-2 infection in utero – A systematic Review. - Palanivelu, Dr. Suvarna; Shunmugavelu, Dr. Karthik (Student's Journal of Health Research Africa, 2024)
Background Maternal viral infections during pregnancy have been associated with adverse neurodevelopmental outcomes in offspring. Although vertical transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is uncommon, maternal immune activation and systemic inflammation may interfere with fetal brain development. Evidence regarding neurodevelopmental outcomes at three years of age following in utero exposure remains heterogeneous. Methods This systematic review was conducted in accordance with the PRISMA 2020 guidelines and registered in PROSPERO (Registration No: TO BE INSERTED). Electronic databases, including PubMed/MEDLINE, Embase, Scopus, Web of Science, and LILACS, were searched up to December 2024. Eligibility criteria included original observational studies reporting neurodevelopmental outcomes in children up to three years of age following confirmed maternal SARS-CoV-2 infection during pregnancy. Seven studies met the inclusion criteria. Results Across the included studies, prenatal exposure to maternal SARS-CoV-2 infection was associated with a higher frequency of neurodevelopmental diagnoses at three years of age compared with non-exposed controls. The most frequently reported domains affected were speech and language development, fine and gross motor skills, and social communication. Increased risk was more consistently observed in male offspring and in children exposed during the third trimester. Several studies reported subtle or no differences during infancy, with developmental disparities becoming more apparent by toddlerhood. Conclusion Prenatal exposure to maternal SARS-CoV-2 infection may be associated with an increased risk of adverse neurodevelopmental outcomes by three years of age, supporting the need for structured developmental surveillance in exposed children. Future research Future studies should incorporate standardized neurodevelopmental assessment tools, stratify outcomes by trimester of exposure and infection severity, control for maternal stress and socioeconomic factors, and include long-term follow-up beyond early childhood.